EXPERIENCE OF APPLICATION IBUPROFEN IN CHILDREN AND THE ADOLESCENT SICK JUVENILE IDIOPATHIC OF THE ARTHRITIS - V.A. Kel’tsev; L.I. Grebenkina (Педиатрическая фармакология)
Results of research of anti-inflammatory action and complications of preparations ibuprofen, nimesulid, diclofenac sodium are submitted at treatment of children and the adolescent suffered from juvenile idiopathic arthritis during the sharp period of disease. Preparations render similar anti inflammatory effect at the given disease. However the least adverse effects are revealed at ibuprofen, that is very important at treatment of children with juvenile idiopathic of an arthritis.Key words: juvenile idiopathic an arthritis, children and adolescent, not steroid anti inflammatory preparations, ibuprofen.